Human resource management practices and organizational performance: The mediation of knowledge management and the moderation of competitive strategies in Jordanian service organizations - Olaimat, Daifalla Eiyadh Nazzal (2014)
This study examined the mediating influence of knowledge management on human resource management (HRM) practices and organizational performance (OP), and the moderating role of competitive strategies on the relationship between knowledge management (KM) and organizational performance. Two-hundred and sixty service organizations in Jordan participated in the survey. Multiple regression and hierarchical multiple regressions were used to test the hypotheses. Results indicated that only three dimensions of HRM practices (i.e. staffing, training and development, and job security) had positive influence on OP. Factor analysis revealed three dimensions of KM: technical, cultural, and human. The results further showed that specific HRM practices were significantly associated with different KM dimensions. Performance appraisal had a positive influence on technical KM, while staffing, performance appraisal, and job security were positively associated with cultural KM. Staffing, training and development, and employee participation and involvement were found to enhance human KM. In addition, different dimensions of KM were found to mediate between different types of HRM practices and OP. Technical KM mediated the relationship between staffing, and training and development and OP, while cultural KM mediated the relationship between staffing and job security, and OP. On the other hand, human KM mediated the relationship between staffing, training and development, and job security, and OP. Finally, competitive strategies interacted with human KM in predicting OP. This study offers several recommendations on how to improve the performance of the service sector in Jordan, discusses limitations of the study, and outlines suggestions for future research.